Analysis Concept And Indicator Proverty in Medan City - Mohammad Yusri (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2020)
Medan government was added to the budget program amount for taking over the poor people a minimum of 10% of the total government budget. The results of the program reveals that the number of poor people in Medan city shows an increase, which is more than poor people still not covered by the government program. The research objectives are 1) analysis of available available concepts to decrease the poor people 2). To Analysis dominand concepts and indicators of proverty in Medan City. Data was collected by using. Sampling area and Purposive Sampling where 294 houses of life that haved a Raskin program are objects of research from 21 subdistricts in Medan city. From descriptive analysis shows that 3 subdistricts were the potential for the program, as follows: Medan Belawan subdistrict, Labuhan subdistrict, and Marelan subdistrict. Three subdistricts are dominant with cultural poor, structural poor, absolute poor, and relatively poor. From the factor analysis found that cultural factors, social factors, social factors, asset factors, and social factors are dominant factors for Medan government to decrease the amount of poor people in Medan City. This research also found that a new factor of proverty program which is a local culture.